Structural, electrical and magnetic properties of bismuth ferrite ceramics substituted with yttrium and indium - Najm, Ammar Abd Ali (2016)
Multiferroic materials demonstrate the simultaneous presence of ferromagnetic, ferroelectric, or ferroelastic orderings. BiFeO3 (BFO) is one of the significant multiferroic materials with high TC ~ 1103 K and TN ~ 643 K at room temperature. BFO suffers high leakage current and weak ferromagnetic and ferroelectric properties. This study was aimed to synthesize BiFe1-xMxO3 (M = Y3+, In3+) samples; where x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8 and 1.0, investigate their phase formation due to Y3+ and In3+ substitution as well as their magnetic and electrical properties. Solid-state technique was used to synthesize BiFe1-xMxO3, (M = Y3+, In3+) using Bi2O3, Fe2O3, Y2O3 and In2O3 as raw materials. XRD, SEM and EDX were used to determine the crystal structure, morphology of the grain size and elemental compositions respectively. Their leakage current, dielectric and magnetic properties were quantified by Keithley source measure unit, Impedance analyzer and VSM respectively. XRD revealed the hexagonal single phase of pure BFO. The phase changed to cubic with Y3+ substitution and BFO remains the primary phase until x = 0.2. Substitution of In3+ promotes the growth of Bi25FeO40, and BFO remains the primary phase until x = 0.4. For SEM results, the average grain size of pure BFO decreased from 2.04 to 0.29 μm with Y3+ substitution, while it decreases to 0.32 μm for In3+ substitution. EDX revealed no impurities in the pure and substituted samples. From magnetic analysis, pure BFO shows antiferromagnetic behavior. A maximum Ms value of 2.9 emu/g and Mr of 0.09 were observed with Y3+ substitution at x = 0.2. The magnetic properties showed nonlinear dependent on In3+ substitution. The highest Ms value of 0.0405 emu/g and Mr of 6.22 × 10-4 emu/g was achieved at x = 0.3. The dielectric measurement showed that the εʹr of the samples increased from 26.5 at x = 0 to 105 at x = 0.4, with Y3+ substitution. The values also improved with In3+ substitution and reached an optimum value of 372 at x = 0.6. The J-E measurement revealed that the leakage current density, J of x = 1.0 (4.6 × 10-8 A/cm2) substituted with Y3+ is decreased significantly by about four order of magnitude compared to that of x = 0 (9.24 × 10-4 A/cm2). Moreover, the J of x = 1.0 (1.51× 10-6 A/cm2) substituted with In3+ is decreased significantly by about three order of magnitude compared to that of x = 0 (9.24 × 10-4 A/cm2). In conclusion, substituted BFO ceramics possess improved dielectric, magnetic properties and has reduced the leakage current. The prepared ceramics could be employed for several applications such as disk read/write heads and ceramic pressure sensor.